Potencial impacto econômico do Programa Nossas Guerreiras no Município de Fortaleza - Oliveira, Angela Dayse Jucá (2024)
Female entrepreneurship is essential for the integration of women into the labor market. In this context, the present study aims to evaluate the "Nossas Guerreiras" Program, which seeks to strengthen the creation of businesses conceived by women, particularly those who are heads of households. The program was proposed and implemented by the Municipality of Fortaleza and is part of the 2022-2025 Multi-Year Plan (PPA). Each participant receives a guided loan of up to 3,000 reais, aiming to formalize their businesses. To analyze the potential impact of the program, the following indicators were used: i) Generation of businesses in low HDI-B neighborhoods; ii) Economic development index; iii) Formalization rate; iv) Sustainability rate of microenterprises; v) Formal job creation rate; vi) Technical qualification performance rate; and vii) Labor market insertion rate. Additionally, the profile of the women who joined the program was analyzed. The results indicate strong participation from the poorer neighborhoods in the creation of new businesses in 2022, and a reduction in participation for 2023. The most recent result can be attributed to the lack of resource allocation from the State to the 'Nossas Guerreiras' program. Despite this, the study demonstrates the potential of female entrepreneurship in Fortaleza as one of the drivers of economic growth, job creation, and social inclusion.